Transplant of ex vivo incubated bone marrow with rIL -7 for the enhancement of immuno-hematopoietic reconstitution. Issue 12 (2nd December 2015) - Abdul-Hai, Ali; Yehuda, Aryeh Ben; Slavin, Shimon; Or, Reuven
Abstract : Interleukin-7 (IL-7) is a critical cytokine in early B and T cell development. Peripheral T cell expansion and thymopoiesis and is a result of the ongoing reconstitution from uncommitted stem cells after transplant. We investigated the efficacy of ex vivo incubated bone marrow cells treated with recombinant human IL-7 (rIL-7) on subsequent in vivo murine models of syngeneic bone marrow (BM) transplant. After ex vivo culture with rIL-7, we observed a 1½-fold increase in BM cellularity; this increase was associated with an enhanced reconstitution of bone marrow cells and thymocytes at 45 days post-transplant. In addition to increased cellularity, lymphocytes from mice transplanted with cultured rIL-7showed enhanced proliferative responses to mitogenic stimulation. These findings suggest rIL-7 to be a promising agent for the clinical application of treating immune deficiency and enhancing immuno-hematopoietic reconstitution of the stem cell auto/allograft.